Global mapping of infectious diseases : methods, examples and emerging applications - Graham, Alastair; Rogers, David J. (David James), 1918-; Hay, S. I. (Simon I.) (Amsterdam : Elsevier, 2006)
This special volume of Advances in Parasitology gives a comprehensive overview of the practical procedures involved in all aspects of global mapping. Coverage includes new research and new data, along with descriptions of new techniques in global mapping. With chapters written by leading experts in the field, it should be a standard for years to come. With an impact factor of 3.9, the series ranks second in the ISI Parasitology subject category. * Includes DVD of global environmental and global population data, including scripts for predicting disease distributions and evaluating the accuracy of these mapped products. * Valuable source of both technical and epidemiological data in this rapidly growing field. * Discusses practical applications of techniques to the study of parasitic and infectious diseases.
Models for vectors and vector-borne diseases / D.J. Rogers -- Global environmental data for mapping infectious disease distribution / S.I. Hay [and others] -- Issues of scale and uncertainty in the global remote sensing of disease / P.M. Atkinson and A.J. Graham -- Determining global population distribution : methods, applications and data / D.L. Balk [and others] -- Defining the global spatial limits of malaria transmission in 2005 / C.A. Guerra, R.W. Snow and S.I. Hay -- The global distribution of yellow fever and dengue / D.J. Rogers [and others] -- Global epidemiology, ecology and control of soil-transmitted helminth infections / S. Brooker, A.C.A. Clements and D.A.P. Bundy -- Tick-borne disease systems: mapping geographic and phylogenic space / S.E. Randolph and D.J. Rogers -- Global transport networks and infectious disease spread / A.J. Tatem, D.J. Rogers and S.I. Hay -- Climate change and vector-borne diseases / D.J. Rogers and S.E. Randolph.
The accompanying DVD contains global environmental and population data.
Includes bibliographical references and index.
Elsevier
Keywords: Medical geography; Geographic information systems; Epidemiology -- Remote sensing; Communicable diseases -- Epidemiology -- Methodology; Parasitic diseases; Parasitology; MEDICAL -- Health Risk Assessment; MEDICAL -- Epidemiology; Infectieziekten; Kartering; Electronic books